SEJARAH PELAKSANAAN UNDANG-UNDANG ISLAM DI PULAU PINANG - Abd Rahim, Mardiana (Jurnal Syariah, 2019)
This article is all attempt to survey as well as to evaluate the development of Islam ill Malaysia ill general and ill Pel/wig ill particular. The illtroductioll of Charter of Justice I. II alld III has somehow affect to the law of lalld ill Penwlg. i.e. Islamic Law. Alld thell its reviews this developmellt ul/til to the recellt years.